Política de Reconhecimento, Raça e Democracia no Brasil - Leonardo Avritzer; Lilian C. B. Gomes (Universidade do Estado do Rio de Janeiro, 2013)
The analysis of the relationship between race and democracy in Brazil requires a specific theoretical approach based on different conceptions of recognition. This article aims to address critically the theories of Nancy Fraser and Axel Honneth in an attempt to deepen the understanding of how a hierarchy of status, which is based on the racial issue and imbricate elements of public, social and private space, was established in Brazil. We point out a number of distinctions in the forms of racial stratification in the United States and Brazil showing that differences can not be reduced to interracial relationships existing in Brazil.We attribute this contrast to the different traditions of legal regulation.We also discussed the different traditions of racial integration and affirmative action in both countries trying to shed light on conceptual lacks of the theories that think racial integration only from the perspective of private sphere.At the end of the paperwe propose a recognition model that integrates the theories of Fraser and Honneth and associates the assigning of legal status to racial segments historically subordinate to a policy that deals with the formation of self-esteem.